2022
DOI: 10.1088/1361-6668/ac8318
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of REBCO CC angular critical current density J c(B, T = 4.2 K, θ) using torque magnetometry up to at least 30 tesla

Abstract: Detailed design of REBCO-based magnets ideally relies on knowledge of the full angular and wide temperature range characterization of the critical current Ic of the REBCO coated conductors (CC) at high magnetic fields. In practice, however, obtaining Ic(B, T, θ) data by the commonly used electrical transport technique is expensive, tedious, and difficult, due to high critical current values that exceed 2000 A for B ‖ ab-plane (θ = 90 deg). The conductors are often damaged during angular transport measurements at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The magnetic field inside the copper tube is parallel to the surface direction of the tapes. The parallel magnetic field could not greatly decay the critical current at 4.2 K [41]. The central magnetic field was calculated by equation ( 7), and the central magnetic field was approximately 0.11 T. Estimations showed that the total critical current of the six-layer CORC conductor at 4.2 K was 35.6 kA and the single coil at 4.2 K could generate a central magnetic field of approximately 0.11 T. It can be noted that, for fusion magnets, the maximum magnetic field design of different coils is completely different, and the influence of external magnetic field on the critical current of the coil should be considered.…”
Section: Estimation Of Critical Current and Magnetic Field At 42 Kmentioning
confidence: 91%
“…The magnetic field inside the copper tube is parallel to the surface direction of the tapes. The parallel magnetic field could not greatly decay the critical current at 4.2 K [41]. The central magnetic field was calculated by equation ( 7), and the central magnetic field was approximately 0.11 T. Estimations showed that the total critical current of the six-layer CORC conductor at 4.2 K was 35.6 kA and the single coil at 4.2 K could generate a central magnetic field of approximately 0.11 T. It can be noted that, for fusion magnets, the maximum magnetic field design of different coils is completely different, and the influence of external magnetic field on the critical current of the coil should be considered.…”
Section: Estimation Of Critical Current and Magnetic Field At 42 Kmentioning
confidence: 91%